Association between red cell distribution width—albumin ratio and all-cause mortality in intensive care unit patients with heart failure - Li, Ni; Li, Junling; Wang, Kai (Frontiers in Cardiovascular Medicine, 2025)
AimThe association between red cell distribution width—albumin ratio (RAR) and the risk of all-cause mortality in intensive care unit (ICU) patients with heart failure remains uncertain. This study aimed to investigate this association.MethodsClinical data from MIMIC-Ⅳ (version 2.2) database was utilized for the analysis of ICU patients with heart failure. Patients were categorized into quartiles (Q1–Q4) based on RAR levels. Kaplan-Meier survival analysis and multivariate adjusted Cox regression models were employed to assess the association between RAR levels and mortality outcomes within 1 year. Subgroup analysis was used to evaluate the prognostic impact of RAR across diverse populations. Restricted cubic spline curves and threshold effect analysis were utilized to quantify the dose-response relationship between RAR levels and mortality. The time-concordance index curve was carried out to explore the additional prognostic value of RAR on mortality over the existing scoring systems, Serial Organ Failure Assessment (SOFA) and Acute Physiology and Chronic Health Evaluation Ⅱ (APACHE Ⅱ).ResultsThe analysis encompassed a cohort of 4,506 patients, with Kaplan-Meier curves indicating that individuals with higher RAR levels exhibited an elevated risk of all-cause mortality (p < 0.001). Multivariate adjusted Cox regression and subgroup analysis demonstrated that individuals in Q2 [hazard ratio (HR) 1.15, 95%CI 0.98–1.34], Q3 (HR 1.65, 95%CI 1.39–1.96) and Q4 (HR 2.16, 95%CI 1.74–2.68) had an increased risk of mortality compared to individuals in Q1 (p for trend < 0.001), and this relationship was consistently observed across most subgroups, except for different ages. Subsequent analysis revealed that the inclusion of RAR significantly improved the prognostic value on the basis of SOFA and APACHE Ⅱ, and the concordance index increased from 0.636 to 0.658 for SOFA, from 0.682 to 0.695 for APACHE Ⅱ (p < 0.001 for both).ConclusionThe study found that high level of RAR was independently associated with an increased risk of 1-year all-cause mortality in ICU patients with heart failure, with a stronger effect in young and middle-aged patients and a threshold effect, which could potentially serve as an early warning indicator for high-risk populations.